APPROACHES TO THE INTERPRETATION OF DIVERSIFICATION OF BUSINESS PROCESSES OF MODERN ENTERPRISES - Касумов, Теймур А. (Journal of Strategic Economic Research, 2024)
In today's globalised world and rapidly changing technologies, the diversification of business processes is becoming an urgent and strategically important task for enterprises. These are approaches, methods and strategies that allow modern enterprises to expand their activities, reducing risks and increasing efficiency. The results of the study were obtained using theoretical analysis of literature sources, the dialectical method of cognition, decomposition, system analysis and synthesis, theoretical generalisations, grouping and systematisation of data to form current and final conclusions. The results of the systematic study clearly show that the diversification of business processes of modern enterprises is increasingly attracting the attention of scholars and practitioners due to the reduction of monopoly pressure on the Ukrainian economy in the context of European integration and the active growth of the level of economy due to the demonopolisation of the Ukrainian economy. Diversification is a strategy chosen by those companies that are trying to survive in the market, increase their profitability, and minimise risks by using the main strategies for diversifying business processes. Based on the theoretical studies, the author proposes a definition of diversification, which is defined in both broad and narrow terms. In the broad sense, it is, first of all, a full-fledged strategy that consists in expanding the activities of an enterprise through the diversity of its activities, including expanding the range of products or services, entering new markets, distributing investments between different types of assets and different areas of production. In a narrow sense, diversification means the distribution of an enterprise's activities between different types of products or markets in order to spread risks and ensure stability in the event of negative factors, which implies a balanced approach to investment in order to avoid significant costs in the event of a negative impact on one part of the business. For further research, a detailed study of specific diversification strategies, their impact on the financial performance of enterprises and an analysis of the introduction of the latest technologies in the diversification process are possible.